CO2 Reduction: Promises of Main Group Metal–Based Nanostructured Materials for Electrochemical CO2 Reduction to Formate (Adv. Energy Mater. 11/2020). Issue 11 (17th March 2020) - Han, Na; Ding, Pan; He, Le; Li, Youyong; Li, Yanguang
Abstract : In article number 1902338, Youyong Li, Yanguang Li and co‐workers review the current status, challenges and future opportunities of main‐group‐metal‐based nanostructured materials for electrochemical CO2 reduction to formate. An emphasis is placed on underlying material design principles for promoting the reaction activity, selectivity and stability. This progress report is expected to provide readers a picture of this quickly evolving field.